2013
DOI: 10.4236/ojog.2013.37096
|View full text |Cite
|
Sign up to set email alerts
|

Low maternal leptin levels in preeclamptic women with fetal growth restriction

Abstract: The risk factors for preeclampsia, extremes of maternal age, changing paternity, concomi-tant maternal autoimmunity, and/or birth intervals greater than 5 years, suggest an underlying immunopathology. We used peripheral blood and lymphocytes from the UteroPlacental Interface (UPI) of 3 rd trimester healthy pregnant women in multicolor flow cytometry-and in vitro suppression assays. The major end-point was the characterization of activation markers , and potential effector functions of different CD4-and CD8 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(30 reference statements)
1
2
0
1
Order By: Relevance
“…As described in Table 2 with the study conducted by Sumawan, et al (19), there was no signiicant correlation between maternal leptin level and birth weight. Factors that inluenced this result were the difference in the number, characteristic, selection criteria for subjects and BMI.…”
Section: The Difference In Maternal Serum Leptin Level Between Preeclsupporting
confidence: 50%
See 1 more Smart Citation
“…As described in Table 2 with the study conducted by Sumawan, et al (19), there was no signiicant correlation between maternal leptin level and birth weight. Factors that inluenced this result were the difference in the number, characteristic, selection criteria for subjects and BMI.…”
Section: The Difference In Maternal Serum Leptin Level Between Preeclsupporting
confidence: 50%
“…The results of this study showed that maternal serum leptin level in preeclampsia increased signiicantly as compared to that in normal pregnancy which is in accordance with previous conducted studies. (19) Some other studies, however, showed different results in which there was a decrease or constant leptin level in preeclampsia. (21) Several other studies showed similar results with this study such as those conducted by Mise,et al (20) and Khosrowbeygi,et al (22), where they found a signiicant increase in maternal serum leptin level in preeclamptic women as compared to normal pregnant women.…”
Section: The Difference In Maternal Serum Leptin Level Between Preeclmentioning
confidence: 97%
“…1 Prevalensi PJT di dunia adalah enam kali lebih tinggi di negara berkembang, 75% di antaranya berada di Asia, Afrika (20%) dan Amerika latin (5%). Di Indonesia, prevalensi rata-rata dari 4 pusat kesehatan ibu dan anak selama periode dari 2004 ke 2005 adalah 4,4%, dengan prevalensi tertinggi (6,44%) dilaporkan di RS Sardjito Yogyakarta 2,3 Salah satu teori utama mengenai penyebab terjadinya pertumbuhan janin terhambat yaitu hasil interaksi plasenta dengan sistem imun maternal, dimana selama kehamilan mengalami kontak langsung dengan fetus yang semi-alogenik. Sel jenis khusus yaitu trofoblas, berasal dari fetus, menginvasi uterus dan kontak langsung dengan sistem imun maternal.…”
Section: Pendahuluanunclassified
“…A number of studies have reported that serum leptin plays a role in the pathogenesis of PE, so that an increase in leptin levels may help prediction of disease and a marker of the severity of PE. Serum Leptin is also known to play a significant role as a biomarker of EOPE and LOPE in relation to the severity of the disease, body mass index (BMI), IUGR and LBW [16]- [18]. Low birth weight and BMI are known to correlate with risk factors for cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%